STRESS ANALYSIS OF STUDENT FORMULA SAEÃâÃÂ® RACE CAR CHASSIS - TRISMAPUTRA (NIM : 13105035); Pembimbing : Prof. Dr. Ir. Indra Nurhadi, ARYA
Student Formula SAE® race car is a racing car designed, built, tested, and competed by students. The design of the race car is limited by the Formula SAE® Rules that published each year. The frame design used in this task is based on Ahmad Syihan design that was written as his final assignment in mechanical engineering, Bandung Institute of Technology. The designed frame is a tubular space frame type with steel as the materials. The frame design are then tested for it feasibility based on analysis of stress arising from operating load. The operating load provided in the form of 3.5g vertical, 1.5g longitudinal and 1.5g lateral acceleration. Frame must be able to withstand the load either by single or combination of these three loading. The analysis was performed with finite element method using Ansys 12 software. Overall, the analysis shows that the von Mises stress of the frame does not exceed the yield stress of steel material. From this analysis result, the frame will experience high von mises stress if it experience a single vertical load or combination with another loading. The safety factor value of the first design is 1.86. This value is great enough so the mass of the chassis could be optimated. The optimization is achived by reducing the part of the chassis that is found unuseful. After the optimization, the cahssis mass of the design is reducing for 8.36 kg and the safety factor of the design become 1.56.